2021
DOI: 10.1002/kpm.1687
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge quality and non‐financial performance—A Malaysian experience

Abstract: This paper proposes a framework that investigates the impact of knowledge quality on innovation in Malaysian manufacturing firms. It explores the effect of innovation on non-financial performance (learning and growth; internal processes) of Malaysian manufacturing companies. Three hundred eighty-eight questionnaires were collected from middle and top engineers, managers, and technicians and were used to conduct the analyses. Structural equation modeling (SEM) is used for testing the developed hypotheses. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In the same research stream. Abdollahbeigi and Salehi (2022) in a study carried out with a representative sample of companies in the manufacturing sector, confirmed that innovation has a significant effect on non-financial performance. These studies corroborate the findings of Saunila (2020) who through a systematic review of the literature enhance understanding of the special characteristics of innovation capability in small business context.…”
Section: Innovation Capability and Financial And Non-financial Perfor...mentioning
confidence: 73%
“…In the same research stream. Abdollahbeigi and Salehi (2022) in a study carried out with a representative sample of companies in the manufacturing sector, confirmed that innovation has a significant effect on non-financial performance. These studies corroborate the findings of Saunila (2020) who through a systematic review of the literature enhance understanding of the special characteristics of innovation capability in small business context.…”
Section: Innovation Capability and Financial And Non-financial Perfor...mentioning
confidence: 73%
“…studies on knowledge quality were directed toward understanding its impacts on innovation in the context of external knowledge sourcing (Corral de Zubielqui et al, 2019;Demirkan et al, 2013) and on firms' innovation capabilities and performance (Abdollahbeigi and Salehi, 2022;Ganguly et al, 2019). Building on the intersection between social capital theory and the KBV, we argue that exploring the role of knowledge quality is crucial to further comprehend the relationship between knowledge sharing, ambidexterity and firm performance.…”
Section: Knowledgementioning
confidence: 98%
“…Although a number of studies have used the KBV of organizations in ambidexterity research, few (if any) have examined if firm’s knowledge quality impacts the relationship between tacit/explicit knowledge sharing and exploitation/exploration processes. Prior studies on knowledge quality were directed toward understanding its impacts on innovation in the context of external knowledge sourcing (Corral de Zubielqui et al , 2019; Demirkan et al , 2013) and on firms’ innovation capabilities and performance (Abdollahbeigi and Salehi, 2022; Ganguly et al , 2019). Building on the intersection between social capital theory and the KBV, we argue that exploring the role of knowledge quality is crucial to further comprehend the relationship between knowledge sharing, ambidexterity and firm performance.…”
Section: Theoretical Background and Frameworkmentioning
confidence: 99%
“…Zhou et al (2022) explored the impact of knowledge transfer among supply chain members on firm innovation and operational performance, and how knowledge quality affects the relationship between them [18]. Abdollahbeigi and Salehi (2021) found that the quality of knowledge significantly affects the innovation of enterprises, and the ability of innovation will have a significant impact on non-financial performance [19]. Ganguly et al (2019) concluded that the transfer of tacit knowledge and the quality of knowledge are positively related to the innovation ability of enterprises [20].…”
Section: Knowledge Qualitymentioning
confidence: 99%